(untitled) (PANGEEA, 2025)
Since the earliest times, people have needed to create records of different information regarding the activities considered to be of maximum importance. In the beginning, this record was related to every family; as society became more and more developed, information was kept at a central level. Man’s most emphasized good was his land, this being of special interest not for the land owners, but for the state organization in order to collect taxes, reason for which, through the present paper, the author would like to present both the evolution and the present information level of the cadastre and Land book operations.